ISOLATION, CHARACTERIZATION AND VALIDATION OF HPLC METHOD FOR QUANTIFICATION OF BIS-[10-(2-METHYL-4H-3-THIA-4,9-DIAZABENZO[F]AZULENE)]-1,4-PIPERAZINE IN AN ANTI-PSYCHOTIC DRUG SUBSTANCE, OLANZAPINE - Bodempudi, Suresh Babu; Rupakula, Ravi Chandra Babu; Reddy, Konda S.; Ghanta, Mahesh Reddy (International Journal of Current Pharmaceutical Research, 2018)
Objective: The main objective of present study was to Isolate, characterize and validate a reverse phase high performance liquid chromatographic method was validated for quantification of bis-[10-(2-methyl-4H-3-thia-4,9-diazabenzo[f]azulene)]-1,4-piperazine in Olanzapine drug substance; it decreases the mental disorders in human body. The method is specific, rapid, precise and accurate for the separation and determination of bis-[10-(2-methyl-4H-3-thia-4,9-diazabenzo[f]azulene)]-1,4-piperazine in Olanzapine drug substance form. Methods: The bis-[10-(2-methyl-4H-3-thia-4,9-diazabenzo[f]azulene)]-1,4-piperazine of Olanzapine was resolved on a Zorbax RX-C 8, 250 mm X 4.6 mm, 5 micron column (L-1) using a mobile phase system containing 0.03 M sodium dodecyl sulphate in water pH 2.5 with 1 N sodium hydroxide solution and acetonitrile in the ratio of (Mobile phase A-52:48 v/v) and (Mobile phase B-buffer and Acetonitrile 30:70 v/v) by using the gradient program. The mobile phase was set at a flow rate of 1.5 ml/min and the volume injected was 20μl for every injection. The detection wavelength was set at 220 nm and the column temperature was set at 35 °C. Results: The proposed method was productively applied for the quantitative determination of bis-[10-(2-methyl-4H-3-thia-4,9-diazabenzo [f]azulene)]-1,4-piperazine in Olanzapine drug substance form. The linear regression analysis data for calibration plots showed a good linear relationship over a concentration range of 0.025to 0.903 µg/ml for bis-[10-(2-methyl-4H-3-thia-4,9-diazabenzo[f]azulene)]-1,4-piperazine, 0.081-0.608 µg/ml for Olanzapine. The mean values of the correlation coefficient were 0.999 and 0.999 for bis-[10-(2-methyl-4H-3-thia-4,9-diazabenzo[f]azulene)]-1,4-piperazine and Olanzapine. The method was validated as per the ICH guidelines. The detection limit (LOD) was about 0.007 µg/ml, 0.024 µg/ml and quantitation limit (LOQ) was about 0.024 µg/ml, 0.081 µg/ml for bis-[10-(2-methyl-4H-3-thia-4,9-diazabenzo[f]azulene)]-1,4-piperazine and Olanzapine. The relative standard deviation was found to be 1.64 % and 2.18 % for bis-[10-(2-methyl-4H-3-thia-4,9-diazabenzo[f]azulene)]-1,4-piperazine and Olanzapine. Conclusion: The validated HPLC method and the statistical analysis showed that the method is repeatable and selective for the estimation of the bis-[10-(2-methyl-4H-3-thia-4,9-diazabenzo[f]azulene)]-1,4-piperazine of the Olanzapine drug substance.